THE STUDENTS' PRIORITY SKILL OF ENGLISH NEEDS BY THE ELEVENTH GRADE STUDENTS AT SMK TORAJA WISATA - Markus Deli Girik Allo; Herni Pabisa (LP2M IAIN Sultan Amai Gorontalo, 2018)
The objective of the research is to find out the student's priority skill of English needs by the eleventh grade students of SMK Toraja Wisata. This research employed non-experimental design. The population of this research was the eleventh grade students of SMK Toraja Wisata academic year 2015/2016, there were 20 students as a population and divided into two department are Perhotelan and Kesehatan department, the sample of the research was the students of Perhotelan department, the researcher used random sampling technique with the numbers of sample was 10 students of Perhotelan department from the eleventh grade students and the writer used one only instrument, namely questionnaire. The result of data analysis collected through the questionnaire showed that from the15 items questionnaire, there are 12 items which speaking occupy the first priority with average value: for questionnaire 1 until 6 with average values 4.50 was important, 4.70, 4.60, 4.50, 4.80 and 4.75 were very important. In the questionnaire 7 and 8 speaking not occupy the first priority because listening and reading occupy the first priority with the average value of 4.70 was very important, and questionnaire 8 with average value 4.60 was very important. Then questionnaire 9 until 12 with average values 4.55 of 4.80, 4.70 were very important, and 4.10 were important. Next questionnaire 13 speaking also not occupy the first priority because listening is occupy the first priority with average value of 4.70 was very important. And the last questionnaire 14 and 15 speaking occupy the first priority with average values 4.90 and 4.90 were very important classification. Based on the data analysis above, it is inferred that the student's priority skill of English needs by the eleventh grade students at SMK Toraja Wisata is speaking.